L-R: Ernestine (Forward) Pike, Ephraim Horwood, Ernest Forward, Hilda (Forward) Pike, Agnes (Horwood) Pratt, Kathleen (Forward) Rorke, Yvonne (Rorke) Pratt, James Rorke, Patricia (Rorke) Yorke, Calvert C. Pratt, Ewart Pratt, James Rorke Jr., Ralph Pike - Rorke Family (1940)
Family members gathered at Heart's Content Barrens to have this group photo taken. Cataloguer's title. Ernest Edward Forward (1859-1944), son of Capt. Mark William Forward and Mary (Bemister) Forward, was born at Carbonear on 29 May 1859. He married Tryphena Butt on 24 June 1885, and had three daughters: Ernestine (Forward) Pike (1887-1950), Hilda Samways (Forward) Pike (1889-1982) and Kathleen (Forward) Rorke (1894-1979). Ernest Forward died on 14 April 1944. His daughter Kathleen (Forward) Rorke (1894-1979) was born at Carbonear on 1 June 1894. She married James Rorke (1890-1947) on 23 May 1917 and had three children: Patricia (Rorke) Yorke (1918-), James Ernest Rorke (1919-2005) and Yvonne (Rorke) Pratt (1922-1998). Kathleen died in 1979. Kathleen's sister Ernestine (Forward) Pike (1887-1950) was born at Carbonear on 24 April 1887. She married Arthur S. Pike at Carbonear on 25 September 1913 and had 3 sons: Ernest Fletcher Pike (1914-1985), Arthur Pike Jr. (1916-1985) and Ralph Forward Pike (1924-1985). She died at Providence, Rhode Island on 22 March 1950. Arthur Pike went on to marry Ernestine's sister Hilda Samways Forward (1889-1982) on 5 June 1951, a little over a year after Ernestine's death. Arthur died around 1980. Yvonne (Rorke) Pratt (1922-1998), youngest child of Kathleen (Forward) Rorke and James Rorke, was born on 4 June 1922. She was the granddaughter of James Addy Rorke and Ernest Edward Forward. Yvonne married Ewart A. Pratt (1919-2000), son of Calvert Coates Pratt (1888-1963) and Agnes (Horwood) Pratt (1888-1952), on 30 October 1943 and had two children: Kathleen Agnes (Pratt) LeGrow and James Rorke Pratt (1949-2000). Yvonne died on 10 March 1998. Ephraim Horwood was Agnes (Horwood) Pratt's father. The Rorke Family Photograph Collection contains 301 black and white and 28 colour photographs of the Rorke Family of Carbonear, Newfoundland, as well as the Forward and Bemister families from that area who are linked to it by marriage. Although spanning from the 1840s-1970s, most photos are ...